“EFFORT TO CREATE COMPANY PERFORMANCE BY INCREASING PERFORMANCE FOR EXTERNAL ENVIRONMENT AND COMPANY RESOURCES WITH COMPETITIVE STRATEGIES AS VARIABLE INTERVENING IN AN EFFORT AT PT. PRIMADAYA ALAM SAKTI BANDUNG AS AUTHOESTRIONEZED CCTV AND MILESTONE XPRO - Rachmawati, Mariana; Natassa, Tezza; Fitriyah, Yasmin; Saudi, Mohd Haizam (CENTRAL ASIA AND THE CAUCASUS, 2022)
This Research Is About How Much Efforts Pt.Primadaya Alam Sakti Bandung As Authorized Partner of Bosch Cctv And Milestone Xprotect Software Makes In Improving Company Performance By Increasing Performance For External Environment And Company Resources With Competitive Strategies. Pt.Primadaya Alam Sakti Bandung As Authorized Partner of Bosch Cctv And Milestone XProtect Software is engaged in the business of installing Security Solutions where the technology used by Bosch Security Systems is to prioritize a total security solution that can combine elements of safety and security at the same time. used descriptive and verification, with hypothesis testing The proposed conceptual model and the research paradigm can be described as a framework for the flow of relationships between variables in the form of a structural equation modeling. Environment And Company Resources With Competitive Strategies As Variable Intervening In An Effort To Increase Company Performance